THE ANALYSIS OF CHARACTERS IN THE NOVELS OF LIFE AND THE SOUND AND THE FURY: A COMPARATIVE ANALYSIS - Orifjonova Sarvinozkhon Azimjon qizi,R.Tillayeva (International Journal of Literature and Language Studies, 2026)
This article provides a comparative analysis of the characters in O‘tkir Hoshimov’s novel "Tushda kechgan umrlar" and William Faulkner’s "The Sound and the Fury". The study examines the psychological world of the protagonists, conflicts between the individual and society, family crises, and issues of moral decline. Similarities and differences in the writers’ artistic approaches to characterization are also discussed.